ANALISIS PENGARUH KOMPONEN INTELECTUAL CAPITAL TERHADAP KEPERCAYAAN DAN REAKSI INVESTOR: STUDI KASUS PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dewantara Satria Yudha; Mohamad Nasir (Diponegoro Journal of Accounting, 2012)
Intellectual capital is recognized as a strategic which gives competitive advantages by corporate resources handling and optimalizing the outcome of intangible and tangible corporate resources. The purpose of this study is to investigate the relation between IC components, and response of investors and investosrs confidence. The Pulic’s Value Added Intellectual Coefficient has been conducted to measure IC and measurement value added and value creation of physical capital, human capital, structural capital and proxy of innovative capital also proxy of relasional capital which are would be the intellectual capital components. This sudy conduct the assumption of the stewardship theory in alternative to value addition according to the stakeholder theory. Data were collected from 2009 – 2010 annual report of 33 listed company on Indonesian Stock Excange which are selected as LQ45. The researchers use the multiple regression to investigate the said relationships. The results does not support the hypothesis that firms’ intellectual capital has a positive impact on investors response (M/B) and investors confidence (CAR) in a modified VAIC method. Furthermore, the result show that Value added capital employed (VACA) positively influences to investors response (M/B), while R&D expenditure has a negatif impact on invesstor response (M/B). The findings show that investors are still consider to physical assets and only focuse on short-term investment performance. Then Advertising Expenditure positively influence investors confidence (CAR).